2022
DOI: 10.7554/elife.77470
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic excitability mechanisms of neuronal ensemble formation

Abstract: Neuronal ensembles are coactive groups of cortical neurons, found in spontaneous and evoked activity, that can mediate perception and behavior. To understand the mechanisms that lead to the formation of ensembles, we co-activated layer 2/3 pyramidal neurons in brain slices from mouse visual cortex, in animals of both sexes, replicating in vitro an optogenetic protocol to generate ensembles in vivo. Using whole-cell and perforated patch-clamp pair recordings we find that, after optogenetic or electrical stimula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 103 publications
3
25
0
Order By: Relevance
“…We also found that the stability of dCA1 coactivity patterns is impaired by the inhibition of LC cells projecting to dCA1 [98]. Importantly, this finding was confirmed by both general pairwise correlations and by methods of cell assembly detection that identify groups of neurons that fire together.…”
Section: Lc Neurons Projecting To Dca1 Regulate Memory Linking By Mod...supporting
confidence: 69%
See 1 more Smart Citation
“…We also found that the stability of dCA1 coactivity patterns is impaired by the inhibition of LC cells projecting to dCA1 [98]. Importantly, this finding was confirmed by both general pairwise correlations and by methods of cell assembly detection that identify groups of neurons that fire together.…”
Section: Lc Neurons Projecting To Dca1 Regulate Memory Linking By Mod...supporting
confidence: 69%
“…Importantly, this finding was confirmed by both general pairwise correlations and by methods of cell assembly detection that identify groups of neurons that fire together. Recent findings suggested that the short-term (minutes to hours) stabilization of neuronal assemblies is mediated by changes in intrinsic excitability [98]. Moreover, dopaminergic modulation of dCA1 leads to increases in neuronal coactivity, post learning reactivation of these coactivity patterns, and improved behavioral performance [99].…”
Section: Lc Neurons Projecting To Dca1 Regulate Memory Linking By Mod...mentioning
confidence: 99%
“…Despite recent efforts to show experimentally that an ensemble also consists of strong, connected neurons (e.g. Alejandre‐García et al., 2022), a clear link is still missing.…”
Section: Introductionmentioning
confidence: 99%
“…While this increased correlated firing and spontaneous reactivations of the stimulated subgroup of neurons over days, the underlying mechanism has remained unclear. Long‐term synaptic plasticity that leads to stronger recurrent inputs is one possibility (Zhang et al., 2020), but a change in the neuron's intrinsic excitability is also possible (Alejandre‐García et al., 2022; Debanne et al., 2019; Zhang & Linden, 2003). Increased intrinsic excitability also plays an important role in memory formation.…”
Section: Introductionmentioning
confidence: 99%
“…These outside sources might be changes in top-down, higher-order thalamic (e.g., from the lateral posterior nucleus, LP / pulvinar) or neuromodulatory input that change the gain of V1 neurons. In addition, individual cells might change their intrinsic excitability 76 . However, were top-down input changes, intrinsic excitability, or neuromodulatory effects the dominant players, we might expect effects on visual responses as well.…”
Section: Discussionmentioning
confidence: 99%